After JAK inhibitor failure: to cycle or to switch, that is the question - data from the JAK-pot collaboration of registries - İNANÇ, GÜZİDE NEVSUN (My University, 2022)
Objectives The expanded therapeutic arsenal in rheumatoid arthritis (RA) raises new clinical questions. The objective of this study is to compare the effectiveness of cycling Janus kinase inhibitors (JAKi) with switching to biologic disease-modifying antirheumatic drug (bDMARD) in patients with RA after failure to the first JAKi. Methods This is a nested cohort study within data pooled from an international collaboration of 17 national registries (JAK-pot collaboration). Data from patients with RA with JAKi treatment failure and who were subsequently treated with either a second JAKi or with a bDMARD were prospectively collected. Differences in drug retention rates after second treatment initiation were assessed by log-rank test and Cox regression analysis adjusting for potential confounders. Change in Clinical Disease Activity Index (CDAI) over time was estimated using a linear regression model, adjusting for confounders. Results 365 cycling and 1635 switching patients were studied. Cyclers were older and received a higher number of previous bDMARDs. Both strategies showed similar observed retention rates after 2 years of follow-up. However, adjusted analysis revealed that cycling was associated with higher retention (p=0.04). Among cyclers, when the first JAKi was discontinued due to an adverse event (AE), it was more likely that the second JAKi would also be stopped due to an AE. Improvement in CDAI over time was similar in both strategies. Conclusions After failing the first JAKi, cycling JAKi and switching to a bDMARD appear to have similar effectiveness. Caution is advised if an AE was the reason to stop the first JAKi.
Keywords: Antirheumatic Agents; Arthritis; Rheumatoid; Therapeutics